Act-belong-commit: Developing strategic plan of sustainable tourism village in Indonesia through NVivo qualitative analysis - Soeswoyo, Dina Mayasari; Dewantara, Made Handijaya (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
Planning is essential in developing a sustainable tourism destination. Good planning will explain the direction, facilitate performance evaluation and minimize negative impacts. This study aims to explore the perspectives of the local community, tourism village developers, policymakers, and experts as a strategic basis for an agriculture-culturally based tourism village development plan. This qualitative research was conducted in 2019-2022, using a case study strategy and an abductive approach. Data were collected through repeated observations, in-depth interviews, a qualitative survey, and literature studies from scientific book, journals, and mass media (websites). Data analysis was carried out qualitatively using CAQDAS NVivo. The results of the study outline the priority strategies for short, medium, and long-term programs in the development of tourism in Cimande Village. This study contributes to other researchers regarding other vital components that must be considered in developing tourism in rural areas, especially those based on culture, namely the commitment and participation of the local community and the local customary system.JEL Classification A13; B55; D69